The study of the modified flocculants properties for whey components isolation - Ulrikh E. (Техника и технология пищевых производств)
The development of scientific bases for isolation of whey components in food enterprises by means of flocculants is an urgent task that makes it possible to solve environmental issues and utilize valuable products (proteins, fat, lactose) that whey contains. The goal of the given work was to study the modified flocculant properties such as swelling and light absorption which have an effect on the completeness of components isolation from milk whey. The research objects of the scientific work were the following: flocculants based on polyacrylamide: Magnafloc 156, Magnaflok 24 and Magnaflok 919; modifiers: propylene glycol, ethylenechlorhydrin, propylene chlorohydrin, amino acids serine and glycine, and whey. The study took place in Kemerovo region. The obtained data reveal that though the swelling degree has approximately the same values, the swelling time of the original and modified flocculants decreases starting with Magnafloc 24 and up to Magnafloc 919. Magnafloc 156, a medium anionic polyelectrolyte with an average degree of macromolecule expansion, is the most optimal among them concerning the swelling rate. The author proved that as a result of modification the flocculants molecular weight increases 1.4–2.4 times. It is established that the average distance between the ends of macromolecules increases 1.3–1.8 times; there is a slight decrease in flexibility; hydrodynamic volume increases 1.33–9.9 times. The author experimentally established that the absorption peaks for the modified flocculants in the ultraviolet region shift to a longer wavelength region compared to the original polyelectrolytes. That indicates that due to the modification process large particle aggregates have been formed. Based on the experiment, the following technological parameters were obtained for milk whey components isolation: flocculant concentration – 0.05%; amount of flocculant – 6 g/m3; temperature – 25–30°C; flocculation time – 10–20 min; feeding method – continuous; settling time – 60 min; angular speed of stirring – 30–40 rpm. The author offered a technological scheme for whey components isolation. It is proved that modified flocculants isolate valuable components from whey much better than unmodified ones.